NUTRITIONAL AND ECONOMIC ANALYSIS OF COCOA AND COFFEE BEAN SKINS IN SILAGE PRODUCTION - Shirleen Samantha Halim; Devi Maulida Rahmah (Agroindustrial Technology Journal, 2024)
Cocoa bean skin and coffee bean skin are biomass waste that is underutilized in Indonesia. Given the nutritional potential of cocoa and coffee bean skin biomass waste, processing it is considered to add potential value. The objective of this research is toinvestigate the potential of utilizing cocoa and coffee bean skin waste in silage production to address specific nutritional requirements. This will be accomplished through the analysis of nutritional characteristics via proximate analysis and the evaluation of economic value added (EVA). Characteristic analysis was carried out with predetermined parameters with raw materials from silage in the form of odot grass, corn husks and additional biomass in the form of cocoa and coffee bean skin waste with concentrations of 20%, 25% and 30% respectively. The results showed that cocoa bean skin silage generally has a higher fat and protein content than coffee bean skin silage. Meanwhile, coffee bean skin silage showed a higher crude fiber and carbohydrate content than cocoa bean skin silage. Economic Value Added (EVA) analysis also revealed that silage generated an added value of IDR 806,018 with a profitability value of 40%, indicating the economic potential in processing biomass waste into silage. Future research can optimize the formulation of biomass waste and explore various biomass sources to improve nutritional and economic benefits. Evaluation of these formulations on various livestock species can also provide valuable insights into their effectiveness in various types of livestock feed